2022
DOI: 10.1108/ijwbr-02-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of wine tourism experience in Mexican wine regions using netnography

Abstract: Purpose This paper aims to offer an experiential segmentation based on the analysis of comments from wine tourists from different Mexican wine regions, using netnography as a data collection and analysis tool. Design/methodology/approach The netnography methodology was applied in three steps: first, collecting consumer opinions (TripAdvisor 1,240 opinions, 2017–2019) from their visits to 20 wineries in four Mexican wine regions. Second, organizing of the data by classifying the various experiences. Third, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In the last decade, wine production in Mexico has increased, in 2018 it was reported that the Mexican wine industry utilized 6,474 hectares, rendering more than 20 million bottles of wine that were distributed by the wineries in 14 states among them Aguascalientes and Querétaro. Querétaro is within the five most important wine producer areas of the country, and the development of wine tourism in Querétaro also promotes the consumption of wine from this region [14,15]. La Redonda is one of the largest producers of wine in Queretaro, with an annual production of 450,000 bottles of which 95 % are placed in the national market and it has been producing quality wine for more than 40 years.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, wine production in Mexico has increased, in 2018 it was reported that the Mexican wine industry utilized 6,474 hectares, rendering more than 20 million bottles of wine that were distributed by the wineries in 14 states among them Aguascalientes and Querétaro. Querétaro is within the five most important wine producer areas of the country, and the development of wine tourism in Querétaro also promotes the consumption of wine from this region [14,15]. La Redonda is one of the largest producers of wine in Queretaro, with an annual production of 450,000 bottles of which 95 % are placed in the national market and it has been producing quality wine for more than 40 years.…”
Section: Introductionmentioning
confidence: 99%